The study of antimicrobial action of combination of ciprofloksacin with antibiotics against polyantibiotic-resistant strains of Pseudomonas aeruginosa by of checkerboard method - Dyachenko, V; Mariushchenko, A; Yagniuk, Yu (Annals of Mechnikov’s Institute, 2020)
Pseudomonas aeruginosa is one of the man caused of opportunistic infections.The rapid decrease in sensitivity of pathogens septic infections to antimicrobial agents has led to significant difficulties in the treatmens of antibioticresistant infections . One solution to this problem is a method of combining antimicrobial medications of different pharmacological groups.Antimicrobial synergy resulting from antibiotic combination therapy is often important in the treatment of serios bacterial infections. Materials and methods. Pseudomonas aeruginosa strains used in this study were isolated from hospital-ised patients at the Hospital of the Surgery of Charkow. The study of combinations of antibiotics efficacy was carried out by determining the minimum inhibitory concentrations using routine method in vitro method "checkeboard". Fractional inhibitory concentration indices were calculated for all isolates with all combi-nations.The present paper investigates the synergic effects of ciprofloksacin in combination with tienam,amikacin or cefepim. Results and discussion. Calculation of the FIX showed that the combination of ciprofloxacin with cefepim demonstrated synergistic inhibitory activity against 66,6 % of P.aeruginosa strains tested. Thus studies have shown the indifferent summation effects of com-binations of ciprofloxacin with tienam or with amika-cin on the mayoriti of multiresistent strains of P.aeruginosa. Conclusion. The result of experimental study by of checkerboard method was shown the high effective-ness of the combinations of ciprofloxacin and cefepime in relation to Pseudomonas aeruginosa poly-antibiotic-resistant strains Pseudomonas aeruginosa is one of the man caused of opportunistic infections.The rapid decrease in sensitivity of pathogens septic infections to antimicrobial agents has led to significant difficulties in the treatmens of antibioticresistant infections . One solution to this problem is a method of combining antimicrobial medications of different pharmacological groups.Antimicrobial synergy resulting from antibiotic combination therapy is often important in the treatment of serios bacterial infections. Materials and methods. Pseudomonas aeruginosa strains used in this study were isolated from hospitalised patients at the Hospital of the Surgery of Charkow. The study of combinations of antibiotics efficacy was carried out by determining the minimum inhibitory concentrations using routine method in vitro method "checkeboard". Fractional inhibitory concentration indices were calculated for all isolates with all combinations.The present paper investigates the synergic effects of ciprofloksacin in combination with tienam,amikacin or cefepim. Results and discussion. Calculation of the FIX showed that the combination of ciprofloxacin with cefepim demonstrated synergistic inhibitory activity against 66,6 % of P.aeruginosa strains tested. Thus studies have shown the indifferent summation effects of combinations of ciprofloxacin with tienam or with amikacin on the mayoriti of multiresistent strains of P.aeruginosa. Conclusion. The result of experimental study by of checkerboard method was shown the high effectiveness of the combinations of ciprofloxacin and cefepime in relation to Pseudomonas aeruginosapolyantibiotic-resistant strains